Inter-joint differences exist in kinetic demand for performance in high jump - Fujimori, T.; Tobe, N.; Sado, N. (ISBS Proceedings Archive (Michigan), 2023)
We aimed to clarify the lower-limb kinetic determinants of inter-individual variability in flight height in the high jump. We hypothesised that although the take-off of the high jump requires great external power, the proximal (hip) joint is required to function as a stabiliser rather than as a power generator for higher performance. We analysed high jump motions by 16 male high jumpers. For the hip joint, only maximum torque significantly correlated with the flight height. Meanwhile, for the knee joint, both peak positive power and peak torque were correlated with the flight height, with a stronger correlation for power than for torque. We found that the kinetic requirement for performance differs between joints, which provides the practical implication that the musculoskeletal functions to be trained differ between joints, such as torque exertion for the hip and power exertion for the knee.